PRODUCTION CHARACTER OF UNIVERSITY PROCESSES - I. V. Markova; N. M. Sheremet (Научный вестник МГТУ ГА, 2021)
The modern tendencies in the Russian system of education, the emergence of competition and market relations in this sphere facilitated the reconsideration of the scientific grounds for the higher educational establishments activity. The suggested theoretical and methodological approaches to the domestic higher educational institutions’ management are subject to debate. The paper analyses the most essential terminology for the theoretical grounds of production management applicable for higher education processes. The terms "production", "activity", "production process" are clarified. The frequently used term "the education services production" is proved to be incorrect. The paper specifies the educational service in the context of the higher educational establishment activity, taking into consideration that the educational service should provide the student with the appropriate knowledge, training management, teaching support and student’s own educational activity control. The educational production process with which the student interfaces is divided into three subsequent stages: preparatory, main and final. The essence of each stage is defined. The students’ and teachers’ educational activity subject and result identification ways are suggested. These ways are aimed at making ultimate decisions for educational establishment production management optimization and other aspects improvement.